Effect of the flash annealing on the impurity distribution and the electronic structure in the inversion layer - Sakata, Tomohiro; Takeda, Sakura Nishino.; Ayob, Nur Idayu; Daimon, Hiroshi (Surface Science Society of Japan, 2015)
We investigated the relationship among the number of flash annealing times to obtain Si clean surface and the change of arsenic dopant concentration and subband levels using secondary ion mass spectroscopy (SIMS) and angle-resolved photoelectron spectroscopy(ARPES). The SIMS result shows that the first five times of the flash annealing already induces significant reduction of the dopant concentration in agreement with the recent work [Pitter et al., J. Vac. Sci. Technol. B 30, 021806 (2012)]. We found the energies of hole subband levels rapidly decrease as the number of the flash annealing times increases. We calculated the subband levels in a broadened confinement potential taking the dopant reduction determined by SIMS into account. The energy separations of the calculated subband levels were in good agreement with the ARPES results. [DOI: 10.1380/ejssnt.2015.75]